Analisis Literasi Digital Siswa dalam Pembelajaran Matematika Berbasis Toy Theater - Moh Zayyadi; Salsabila Apsari Junaidi (Universitas Islam Jember, 2026)
This study aims to analyze students’ digital literacy in mathematics learning using Toy Theater media among fifth-grade elementary school students, involving 20 participants. The study employed a descriptive quantitative approach supported by qualitative data. Data were collected through questionnaires as the primary source, while interviews and documentation were used to strengthen the analysis. Students’ digital literacy was analyzed based on four aspects: learning attitude, social-emotional, technical, and cognitive. The results showed that the learning attitude aspect reached 90.4% and the social-emotional aspect 89%, both categorized as very high, while the technical aspect reached 78.6% and the cognitive aspect 84.2%, both categorized as high. Interview findings indicated that the use of Toy Theater supported students’ enthusiasm and engagement in mathematics learning, while students’ work demonstrated that the interactive digital media helped them understand mathematical concepts. Therefore, Toy Theater has the potential to support students’ digital literacy in mathematics learning, although teacher guidance is still needed during the initial stages of using the media. Keywords: Digital literacy, Toy Theater